Reduce Anxiety Levels with the Cupping Method - Husnul Khotimah; Putri Inni Khozaimah; Raudatul Jannah; Innani Kholidatul Jannah; Siti Qomariyatul Ulfa; Sumiati Aristi (Global Health Science Group, 2021)
The COVID-19 pandemic is a non-natural disaster that can have an impact on everyone's mental and psychosocial health conditions. According to WHO (2020), the emergence of a pandemic causes anxiety at various levels of society. Anxiety management consists of pharmacological and non-pharmacological therapy. One of the non-pharmacological therapies that can be used is wet cupping. Cupping will stimulate the secretion of the hormone -endorphin which will have an anti-pain and anxiolytic (anti-anxiety) effect. The method used in the introduction of the cupping method as a decrease in anxiety levels is to conduct lectures and discussions which are attended by female students of the Nurul Jadid Islamic Boarding School, especially in the Az-Zainiyah Region. To respond to the COVID-19 pandemic, not a few of the community, especially in Islamic boarding schools, are experiencing concerns or feelings of anxiety, so counseling related to cupping therapy is carried out to students at Nurul Jadid Islamic Boarding School. This counseling aims to provide new knowledge to students that cupping is one way to reduce anxiety. There are 30 students from various institutions who are participants in this counseling who can understand and become new knowledge from the results of the reviews given. students were so enthusiastic to know about cupping therapy in reducing anxiety levels with some critical questions that were asked in counseling activities, with that the students had new knowledge in the health field.